2020
DOI: 10.1139/cjfr-2019-0102
|View full text |Cite
|
Sign up to set email alerts
|

Fusing diameter distributions predicted by an area-based approach and individual-tree detection in coniferous-dominated forests

Abstract: An area-based approach (ABA) is the most common method used to predict forest attributes with airborne laser scanning (ALS) data. Individual-tree detection (ITD) offers an alternative to ABA; however, few studies have examined the selection of these two alternatives for the prediction of diameter distributions. We predicted diameter distributions by applying ABA and ITD in coniferous-dominated boreal forests using ALS data and examined their predictive performance based on the shapes of the diameter distributi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Several studies have used ABA to describe the relationship between forest variables and ALS metrics. These include the prediction of ℎ, basal area, volume, biomass or height using linear regression (Means et al 2000;Naesset 2002), non-linear regression (Packalén et al 2011) or non-parametric approaches (Packalén and Maltamo 2006;Yu et al 2010;Andersen et al 2011;Räty et al 2020). Some studies have also identified the factors that affect the performance of ABA, such as plot size (Gobakken and Naesset 2008), sample size (Junttila et al 2013), errors in plot positions (Gobakken and Naesset 2009;Rana et al 2014), and the resolution of the cell (Packalen et al 2019).…”
Section: Area-based Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have used ABA to describe the relationship between forest variables and ALS metrics. These include the prediction of ℎ, basal area, volume, biomass or height using linear regression (Means et al 2000;Naesset 2002), non-linear regression (Packalén et al 2011) or non-parametric approaches (Packalén and Maltamo 2006;Yu et al 2010;Andersen et al 2011;Räty et al 2020). Some studies have also identified the factors that affect the performance of ABA, such as plot size (Gobakken and Naesset 2008), sample size (Junttila et al 2013), errors in plot positions (Gobakken and Naesset 2009;Rana et al 2014), and the resolution of the cell (Packalen et al 2019).…”
Section: Area-based Approachmentioning
confidence: 99%
“…Some studies have also identified the factors that affect the performance of ABA, such as plot size (Gobakken and Naesset 2008), sample size (Junttila et al 2013), errors in plot positions (Gobakken and Naesset 2009;Rana et al 2014), and the resolution of the cell (Packalen et al 2019). However, this method is most often applied in operational forest inventories that employ ALS data (Maltamo et al 2014), and is more flexible and robust for diameter predictions, for example, in boreal managed forests dominated by coniferous species (Räty et al 2020).…”
Section: Area-based Approachmentioning
confidence: 99%
“…Following previous research [26,32,33,35,43,44], 46 ALS features were calculated for each segment (Figure 3VIII). Height metrics were calculated considering points above 2 m. Intensity metrics were calculated considering points above the 85th height percentile inside segments for both channels (C1 and C2).…”
Section: Calculation Of Metricsmentioning
confidence: 99%
“…Machine learning techniques were also used to predict individual tree DBH [34]. The ABA and ITD approaches were also combined to predict SSD by fusing the two predicted SSDs [35], employing distribution matching techniques [36], using replacement or histogram matching methods [37], or even using stand density and crown radius distribution through a distribution matching step [38]. Secondly, the interest in SSD estimation was focused on more complex forests, especially deciduous and tropical stands.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation